Classification improvement of impact factors of micro-level on activity of maritime enterprises - Maryna Kovbatyuk; Viktoryia Shklyar (Cхід, 2013)
Modern condition of development of transport enterprises is in poor condition, caused by the global economic crisis. Enterprises of maritime transport are especially sensitive to negative tendencies. They belong to infrastructure and dramatically depend on economic condition of the country.